Days to return to participation after a hamstrings strain among American collegiate soccer players - Cross, K. M.; Saliba, S. A.; Conaway, M.; Gurka, K. K.; Hertel, J. (Journal of Athletic Training, 2015)
Context: Among US collegiate soccer players, the incidence rate and the event characteristics of hamstrings strains differ between sexes, but comparisons in the return-to-participation (RTP) time have not been reported.